The Photocatalytic Conversion of Carbon Dioxide to Fuels Using Titanium Dioxide Nanosheets/Graphene Oxide Heterostructure as Photocatalyst - Apisit Karawek; Kittipad Kittipoom; Labhassiree Tansuthepverawongse; Nutkamol Kitjanukit; Wannisa Neamsung; Napat Lertthanaphol; Prowpatchara Chanthara; Sakhon Ratchahat; Poomiwat Phadungbut; Pattaraporn Kim-Lohsoontorn; Sira Srinives (Nanomaterials, 2023)
Carbon dioxide (CO2) photoreduction to high-value products is a technique for dealing with CO2 emissions. The method involves the molecular transformation of CO2 to hydrocarbon and alcohol-type chemicals, such as methane and methanol, relying on a photocatalyst, such as titanium dioxide (TiO2). In this research, TiO2 nanosheets (TNS) were synthesized using a hydrothermal technique in the presence of a hydrofluoric acid (HF) soft template. The nanosheets were further composited with graphene oxide and doped with copper oxide in the hydrothermal process to create the copper−TiO2 nanosheets/graphene oxide (CTNSG). The CTNSG exhibited outstanding photoactivity in converting CO2 gas to methane and acetone. The production rate for methane and acetone was 12.09 and 0.75 µmol h−1 gcat−1 at 100% relative humidity, providing a total carbon consumption of 71.70 µmol gcat−1. The photoactivity of CTNSG was attributed to the heterostructure interior of the two two−dimensional nanostructures, the copper−TiO2 nanosheets and graphene oxide. The nanosheets−graphene oxide interfaces served as the n−p heterojunctions in holding active radicals for subsequent reactions. The heterostructure also directed the charge transfer, which promoted electron−hole separation in the photocatalyst.